Error Estimates in Balanced Norms of Finite Element Methods on Shishkin Meshes for Reaction-Diﬀusion Problems - R. Hans-G. (Моделирование и анализ информационных систем)
Error estimates of ﬁnite element methods for reaction-diﬀusion problems are often realized in the related energy norm. In the singularly perturbed case, however, this norm is not adequate. A diﬀerent scaling of the H1 seminorm leads to a balanced norm which reﬂects the layer behavior correctly.